The Orbit of Communications - Phillip Alampi (Journal of Applied Communications, 1969)
Whenever I contemplate the situation confronting us throughout the word, in America and even occasionally in my own state of New Jersey, I long for someone to tell me where we, the people of this world, shall be tomorrow, a decade or a century hence.